2011
DOI: 10.1002/fld.2593
|View full text |Cite
|
Sign up to set email alerts
|

A comparative investigation of hydrofoil at angles of attack

Abstract: SUMMARYIn this paper, a numerical investigation of incompressible flow around a hydrofoil is presented. The laminar flow was modeled at different angles of attack. Momentum and continuity equations were coupled by the artificial compressibility scheme. In finite-volume method, convective fluxes were calculated and compared by four schemes. Flux averaging with pressure correction was used. The other characteristic-based (CB) methods consisted of Roe scheme and original CB scheme. A revised CB scheme was impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The number of iterations to achieve steady state is reduced by using a variable time step that depends on the local flow changes and the grid spacing as [13] Dt ¼…”
Section: Time Discretizationmentioning
confidence: 99%
“…The number of iterations to achieve steady state is reduced by using a variable time step that depends on the local flow changes and the grid spacing as [13] Dt ¼…”
Section: Time Discretizationmentioning
confidence: 99%
“…The pressure‐based modification for the convective fluxes includes where, R and L indicate right and left cells respectively and p is used as a driving force . The first and higher accuracy can be achieved in Equation .…”
Section: Governing Equationsmentioning
confidence: 99%
“…The fifth‐order Runge–Kutta has a higher stability range ( CFL ≤ 3), which has been used for time discretization in the present study where Q includes the discretized form of integral convective and viscous terms. The number of iterations to achieve steady state is reduced by using a variable time step that depends on the local flow changes and the grid spacing as where Δ t shows the local time step.…”
Section: Time Dicretization and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparative studies of the original and revised CBM revealed that both the methods demonstrate the same performances in terms of accuracy and convergence rate. 16,17 Razavi et al 13 suggested that the slow convergence of the CBM originates from the assumption of local one-dimensionality of wave propagation parallel to the grid normals, in which the effects of disturbances traveling along other directions are excluded. Their hypothesis was based on the similar problem observed previously in the gridaligned compressible upwind schemes.…”
Section: Introductionmentioning
confidence: 99%